PENGEMBANGAN KEMAMPUAN BAHASA ANAK MELALUI METODE BERCERITA PADA KELOMPOK B DI PAUD HINDU DHARMA SASTRA, DESA PELAGA, KECAMATAN PETANG KABUPATEN BADUNG TAHUN 2020/2021 - Narsi Ni Wayan (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2021)
Early childhood education is the first and foremost education so learning must also be considered because the most rapid stage of development is at an early age. One thing that must be developed at an early age is the child's language skills. Language ability is an important ability for early childhood because it is related to the child's ability to listen, communicate, think and form relationships with other people. Stimulating language skills must be done with appropriate stimulation and provide opportunities for children to express their opinions. One way to stimulate children's language skills is the storytelling method. The storytelling method is an activity to tell stories in front of children and provide appropriate stimulation for the development of children's language skills. The theories used to analyze the problem are constructivism theory, behaviorism theory and learning theory. This study uses a qualitative research type. The research subjects used were group B class teachers, group B students. The data collection methods were participant observation, structured interviews, document studies and literature studies. Data analysis methods used are data reduction, data classification and data presentation. The results showed that the learning process carried out in PAUD Hindu Dharma Sastra was carried out through three stages consisting of the planning stage, the implementation stage and the evaluation stage. The application of the storytelling method in developing children's language skills also encountered obstacles consisting of internal and external factors. Internal factors include children getting bored quickly, different abilities of children and less stimulation of children's concentration power. External factors are the lack of facilities and infrastructure and the lack of parental involvement in school programs. In overcoming these obstacles, efforts are needed. The efforts to overcome the obstacles in developing children's language skills through the storytelling method in PAUD Hindu Dharma Sastra are the use of gestures and the participation of children, using media in stories, and providing the right motivation to children.